Surveillance Strategies and Prevention of Flavivirus Infections in (Zoo-) Birds in Germany - Bergmann, Felicitas (Tierärztliche Hochschule Hannover, 2023)
Two flaviviruses (Usutu virus (USUV) and West Nile virus (WNV)) are known to cause disease and deaths in the avifauna as well as in humans. USUV and WNV circulate in an enzootic cycle between birds (amplification/reservoir hosts) and competent mosquitoes (vectors). Mammals such as equines and humans are classified as dead-end hosts and can display severe clinical signs. USUV has spread across the African and European continents, while WNV is present worldwide (with the exception of Antarctica). Since their introduction into Germany (USUV 2010/2011; WNV 2018), both viruses are considered endemic and are spreading continuously. USUV has spread throughout Germany, while WNV occurs primarily in eastern Germany but also shows clear tendencies to spread to the north-west. This highlights the need for serological and molecular biological surveillance of WNV and USUV in susceptible hosts (birds) as well as dead-end hosts (horses) to track current events. In addition, this doctoral thesis addresses the possibility of protecting valuable zoo and breeding birds in endemic areas from severe WNV infections using an approved inactivated equine vaccine. The first study (Manuscript I) focused on sampling zoo birds (mainly owls) from the Wildpark Schwarze Berge, located in northern Lower Saxony on the border to Hamburg, over four years (2018–2022). USUV genomes were found during the study period, in addition to serological USUV detections. In certain bird species, USUV neutralizing antibodies (nAbs) were tracked over the entire four-year period. These collected data are therefore very important and unique as so far no studies have tracked the progression of USUV antibodies in naturally infected birds over several years. Furthermore, the introduction of WNV was recently demonstrated serologically for the first time, confirming the steady spread of this virus to the north-west of the country. The WNV seroprevalence in a clinical horse cohort in an endemic area (Berlin/Brandenburg, BE/BB) was compared to that of a previously ...